1992
DOI: 10.1093/nar/20.7.1487
|View full text |Cite
|
Sign up to set email alerts
|

Reverse transcriptase inhibits Taq polymerase activity

Abstract: Detection of viral RNA by polymerase chain reaction (PCR) requires the prior reverse transcription of the viral RNA. In order to minimise the number of manual manipulations required for processing large numbers of samples, we attempted to design a system whereby all the reagents required for both reverse transcription and amplification can be added to one tube and a single, non-interrupted thermal cycling program performed. Whilst attempting to set up such a one-tube system with Taq polymerase (Taq; Biotech In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 12 publications
2
66
1
1
Order By: Relevance
“…Previous studies have shown that the activity of Taq polymerase is reduced by an active reverse transcriptase (Sellner et al, 1992). It was recommended therefore to inactivate the reverse transcriptase, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the activity of Taq polymerase is reduced by an active reverse transcriptase (Sellner et al, 1992). It was recommended therefore to inactivate the reverse transcriptase, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This format allowed optimal amplification with little or no nonspecific amplification of contaminating DNA, as determined by the absence of bands when RT was excluded. After amplification, the sample (20 l) was separated on a 2% agarose gel containing 0.3 g/ml (0.003%) of ethidium bromide, and bands were visualized and photographed using a UV transilluminator (33)(34)(35).…”
Section: Total Rna Isolation and Rt-pcr Amplificationmentioning
confidence: 99%
“…24 RT-PCR for bcl-X L and bcl-X S was performed using gene-specific primers that span all of the known splice sites: murine bcl-X sense (5Ј-TGGTC- . Expected band sizes were 557 bp for bcl-X L and 317 bp for bcl-X S .…”
Section: Rt-pcrmentioning
confidence: 99%